Excitation Energy Transfer and Exchange‐Mediated Quartet State Formation in Porphyrin‐Trityl Systems. Issue 8 (1st December 2020) - Nolden, Oliver; Fleck, Nico; Lorenzo, Emmaline R.; Wasielewski, Michael R.; Schiemann, Olav; Gilch, Peter; Richert, Sabine
Abstract: Photogenerated multi‐spin systems hold great promise for a range of technological applications in various fields, including molecular spintronics and artificial photosynthesis. However, the further development of these applications, via targeted design of materials with specific magnetic properties, currently still suffers from a lack of understanding of the factors influencing the underlying excited state dynamics and mechanisms on a molecular level. In particular, systematic studies, making use of different techniques to obtain complementary information, are largely missing. This work investigates the photophysics and magnetic properties of a series of three covalently‐linked porphyrin‐trityl compounds, bridged by a phenyl spacer. By combining the results from femtosecond transient absorption and electron paramagnetic resonance spectroscopies, we determine the efficiencies of the competing excited state reaction pathways and characterise the magnetic properties of the individual spin states, formed by the interaction between the chromophore triplet and the stable radical. The differences observed for the three investigated compounds are rationalised in the context of available theoretical models and the implications of the results of this study for the design of a molecular system with an improved intersystem crossing efficiency are discussed. Abstract : Photogenerated multi‐spin systems composed of a porphyrin chromophore and a trityl radical are investigated with respect to their optical and magnetic properties. Profiting from the time‐resolution of fs‐TA spectroscopy and the capability of EPR to distinguish near‐degenerate states with different spin multiplicity, this work reports unique insight into the excited‐state reaction mechanism and suggests improvements to the molecular design in view of applications in the fields of molecular spintronics and artificial photosynthesis.